A RaPID way to discover nonstandard macrocyclic peptide modulators of drug targets. Issue 12 (16th January 2017) - Passioura, Toby; Suga, Hiroaki
Abstract : Discovery of tRNA-aminoacylating ribozymes and their use for genetic code reprogramming and peptide drug discovery. Abstract : Studies of the fundamental nature of RNA catalysis and the potential mechanism of a shift from the "RNA world" to proteinaceous life lead us to identify a set of ribozymes (flexizymes) capable of promiscuous tRNA acylation. Whilst theoretically and mechanistically interesting in their own right, flexizymes have turned out to have immense practical value for the simple synthesis of tRNAs acylated with unusual amino acids, which in turn can be used for the ribosomal synthesis of peptides containing non-canonical residues. Using this technique, it is possible to synthesise peptides containing a range of structural features (macrocyclic backbones, backbone N -methylation, d -stereochemistry, etc. ) commonly observed in natural product secondary metabolites, a chemical class that has historically been a rich source of drug-like molecules. Moreover, when combined with biochemical display screening technologies, this synthetic approach can be used to generate (and screen for target affinity) extremely diverse (in excess of 10 12 compound) chemical libraries, making it an extraordinary tool for drug discovery. The current review charts the history of flexizyme technology and its use for non-canonical peptide synthesis and screening.